Bacterial versus non-bacterial infections: a methodology to support use-case-driven product development of diagnostics. Issue 10 (21st October 2020) - Escadafal, Camille; Geis, Steffen; Siqueira, A M; Agnandji, Selidji T; Shimelis, Techalew; Tadesse, Birkneh Tilahun; Massinga Loembé, Marguerite; Harris, Victoria; Fernandez-Carballo, B Leticia; Macé, Aurélien; Ongarello, Stefano; Rodriguez, William; et al.
Abstract : Acute febrile illness (AFI) is one of the most common reasons for seeking medical care in low-income and middle-income countries. Bacterial infections account for a relatively small proportion of AFIs; however, in the absence of a simple diagnostic test to guide clinical decisions, healthcare professionals often presume that a non-malarial febrile illness is bacterial in origin, potentially resulting in inappropriate antibiotic use. An accurate differential diagnostic tool for AFIs is thus essential, to both limit antibiotic use to bacterial infections and address the antimicrobial resistance crisis that is emerging globally, without resorting to multiple or complex pathogen-specific assays. The Biomarker for Fever-Diagnostic (BFF-Dx) study is one of the largest fever biomarker studies ever undertaken. We collected samples and classified disease aetiology in more than 1900 individuals, distributed among enrolment centres in three countries on two continents. Identical protocols were followed at each study site, and the same analyses were conducted in each setting, enabling like-with-like comparisons to be made among the large sample set generated. The BFF-Dx methodology can act as a model for other researchers, facilitating wider utility of the work in the future. The established sample collection is now accessible to researchers and companies and will facilitate the development of future fever-related diagnostic tests. Here, we outline the methodology used to determine the sample populations and to differentiate bacterial versus non-bacterial AFIs. Future publications will set out in more detail the study's demographics, the causes of fever identified and the performance of selected biomarkers.